Apatite Formation: Why It May Not Work as Planned, and How to Conclusively Identify Apatite Compounds. (29th July 2013) - Drouet, Christophe
Abstract : Calcium phosphate apatites are inorganic compounds encountered in many different mineralized tissues. Bone mineral, for example, is constituted of nanocrystalline nonstoichiometric apatite, and the production of "analogs" through a variety of methods is frequently reported. In another context, the ability of solid surfaces to favor the nucleation and growth of "bone-like" apatite upon immersion in supersaturated fluids such as SFB is commonly used as one evaluation index of the "bioactivity" of such surfaces. Yet, the compounds or deposits obtained are not always thoroughly characterized, and their apatitic nature is sometimes not firmly assessed by appropriate physicochemical analyses. Of particular importance are the "actual" conditions in which the precipitation takes place. The precipitation of a white solid does not automatically indicate the formation of a "bone-like carbonate apatite layer" as is sometimes too hastily concluded: "all that glitters is not gold." The identification of an apatite phase should be carefully demonstrated by appropriate characterization, preferably using complementary techniques. This review considers the fundamentals of calcium phosphate apatite characterization discussing several techniques: electron microscopy/EDX, XRD, FTIR/Raman spectroscopies, chemical analyses, and solid state NMR. It also underlines frequent problems that should be kept in mind when making "bone-like apatites."